2019
DOI: 10.2337/db19-0554
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Amylase Expression in Control, Autoantibody-Positive, and Type 1 Diabetes Pancreatic Tissues

Abstract: Within the human pancreas, exocrine and endocrine cells control secretion of digestive enzymes and production of hormones to maintain metabolic homeostasis, respectively. While the vast majority of type 1 diabetes research efforts have focused on endocrine function and autoimmunity, recent studies identified a series of unique features (e.g., reduced weight and volume, increased density of leukocytes) within the exocrine pancreas in this disease, but the mechanisms underlying these aberrancies are unknown. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
(19 reference statements)
1
23
0
Order By: Relevance
“…The mean acinar cell nuclei density was marginally higher in Exo1 than in Exo3 in the pancreas of non-diabetic subjects (figure 1C); however, no difference could be determined between Exo1 and Exo3 within the pancreas of type 1 diabetic subjects (figure 1D). Amylase-negative acinar regions were found in FFPE but not in frozen tissue Amylase-negative acinar regions (figure 2A-C), as described by Kusmartseva et al, 18 were found by immunohistochemistry (IHC) with three different antibodies against amylase on FFPE tissue from 3/7 donors with type 1 diabetes and 1/8 non-diabetic controls. The same phenomenon was not evident by IF of frozen sections from the same donors, where an even expression of amylase was seen in acinar cells throughout the exocrine parenchyma (figure 2D).…”
Section: Resultssupporting
confidence: 60%
“…The mean acinar cell nuclei density was marginally higher in Exo1 than in Exo3 in the pancreas of non-diabetic subjects (figure 1C); however, no difference could be determined between Exo1 and Exo3 within the pancreas of type 1 diabetic subjects (figure 1D). Amylase-negative acinar regions were found in FFPE but not in frozen tissue Amylase-negative acinar regions (figure 2A-C), as described by Kusmartseva et al, 18 were found by immunohistochemistry (IHC) with three different antibodies against amylase on FFPE tissue from 3/7 donors with type 1 diabetes and 1/8 non-diabetic controls. The same phenomenon was not evident by IF of frozen sections from the same donors, where an even expression of amylase was seen in acinar cells throughout the exocrine parenchyma (figure 2D).…”
Section: Resultssupporting
confidence: 60%
“…Abnormalities of the pancreatic exocrine function in T1D have recently received renewed attention, because of their potential role in the pathogenesis of the disease, [13][14][15][16][17][18][19][20][21][22][23] having been detected also during the presymptomatic phase of T1D, that is, in islet autoantibody positive individuals. 15-17 20-23 Our findings confirm the evidence of some degree of impairment of the pancreatic exocrine function in patients with T1D, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the involvement of the exocrine component of the pancreas in the pathogenesis of T1D has been revisited, based on the accumulation of evidence, including reduction of pancreatic volume, 10 13–15 and estimated weight, 16 17 intraparenchymal neutrophil and monocyte infiltration, 18–20 peri-islet fibrosis and acinar atrophy, 21 reduction of circulating trypsinogen 22 and trypsin, 8 and altered amylase expression patterns. 23 Interestingly, many of these abnormalities were observed already during the presymptomatic phase of the disease, that is, in individuals with normal glucose tolerance, although positive for circulating islet autoantibodies, 15–17 20 22 23 suggesting that these features are associated with the pathogenesis of T1D, rather than secondary to its metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the degree of pancreas reduction in both type T1D and T2D far exceeds the volume of the endocrine pancreas, suggesting exocrine involvement in diabetes pathogenesis. These imaging findings are supported by histological studies of the pancreas from T1D donors which found reduced numbers of acinar cells (16) and altered exocrine cell expression (17) versus controls. Investigations into the temporal dynamics of pancreas size in T1D have found reduced pancreas size at diagnosis (18,19), in individuals at risk for disease (20,21), and longitudinal declines over the course of disease (20).…”
Section: Pancreas Volumementioning
confidence: 57%